Ethnobotany and Food Plant Community Sambori District Bima Regency West Nusa Tenggara Indonesia - Zulharman Zulharman; Bagyo Yanuwiadi; Jati Batoro (Natural B, Journal of Health and Environmental Sciences, 2015)
The purpose of the study was to determine the local knowledge that is applied by the local people in Sambori village in the utilization of medicinal plants and food plants. The research was conducted in the Sambori village, District of Lambitu, Bima, West Nusa Tenggara, in January to February 2015. The method was employed through ethnographic description through interviews and literary study. The method to select the informants was using the snowball technique. The main characteristics of respondent are the public figure and Sambori traditional people of 30 people. Data analysis was analyzed of ethnographic descriptive analysis. The results showed that the number of plants used for the mediclinal purposes was 18 species of plants, which are dominated by species of Zingiberaceae family, with specific benefits for three types of fever treatment, 9 species for smallpox, and 9 species for kidney stones, and 9 species for slimming and maag. The utilization of plants for daily food consists of 8 species namely Oryza sativa, Oryza sp, Zea mays, Vigna Radiata, Manihot utilisima, Glycine max, Arachis hypogaea L dan Ipomoea batatas L. The material of food plants consists of three families, 38% was dominated by Poaceae family food plants, 37% of Fabaceae family and 25% of Convolvulaceae family. The food plants that utilized for vegetables material are 9 types species, namely Vigna sinensis, Momordica charantia, Sechium edule, Cucumis sativus, Phaseolus vulgaris, Solanum lycopersicum, Schleichera oleosa, Solanum melongena dan Capsicum frutescens L. The parts of the food plants as vegetables are leaves and fruits.